Climate change through the eyes of a chemist, energy, technologist - Anatoliy Zhukov; Sergey Gushcha; Elena Bobro (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
In this article, the author made an attempt to present and analyze issues related to global environmental problems, and in particular, the role of carbon dioxide in global warming. Well-known facts and unexpected findings are intended to awaken in the reader a critical attitude towards the prevailing beliefs in these matters. From the point of view of a chemist, the reality of extracting CO2 from air and converting it back into fuel is assessed. Simple energy calculations make it possible to assess the ability of "green" energy to replace carbon and influence the climate warming process. And finally, the key proposals are presented from the point of view of a technologist, since it is technologists who make real and implement the most daring discoveries and projects of scientists and inventors.